2018
DOI: 10.1136/bcr-2017-220858
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-cell lymphoma mimicking classic Hodgkin’s lymphoma in a patient presenting with fevers of unknown origin

Abstract: A 52-year-old man presented to our hospital for further workup of fever of unknown origin after an extensive workup at an outside hospital had failed to reveal a diagnosis. At the outside hospital, he underwent excisional biopsy of the left supraclavicular lymph node, which showed non-necrotising granulomatous changes, and a bone marrow biopsy which showed a normocellular marrow. He was discharged without a diagnosis with recommendations to present to a tertiary hospital. During his admission, his hospital cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The case was treated as Hodgkin lymphoma, which then recurred, only to be diagnosed as angioimmunoblastic lymphoma on a subsequent biopsy. Butler et al 14 reported a similar case of a patient in their 50s who presented with pyrexia of unknown origin. It was earlier misdiagnosed as Hodgkin lymphoma; however, a subsequent excisional biopsy revealed PTCL with RS-like cells.…”
Section: Discussionmentioning
confidence: 94%
“…The case was treated as Hodgkin lymphoma, which then recurred, only to be diagnosed as angioimmunoblastic lymphoma on a subsequent biopsy. Butler et al 14 reported a similar case of a patient in their 50s who presented with pyrexia of unknown origin. It was earlier misdiagnosed as Hodgkin lymphoma; however, a subsequent excisional biopsy revealed PTCL with RS-like cells.…”
Section: Discussionmentioning
confidence: 94%